KONTRIBUSI POWER OTOT LENGAN DAN KOORDINASI MATA DAN TANGAN TERHADAP KEMAMPUAN THROW IN SEPAKBOLA PADA PEMAIN SSB DURI GALAXY U-17 - Ismail, Ismail; Ramadi, Ramadi; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of this research is to investigate how arm muscle power and hand-eye coordination contribute to the soccer throw-in ability of SSB Duri Galaxy U-17 players. This research uses a type of correlation by calculating the level of relationship between several different variables. The data collection method uses tests and measurements on the research sample, namely 24 SSB Duri Galaxy U-17 players. The tests used are arm muscle power tests: overhead medicine ball throw, hand-eye coordination test and throw-in test. The data analysis technique used is calculating correlation values. Based on the results of the research and discussion, it can be concluded that: (1) There is a contribution of arm muscle power to the soccer throw-in ability of SSB Duri Galaxy U 17 players with a calculated r value = 0.535 and an r table value of 0.396, amounting to 28.62% (2) There is the contribution of eye and hand coordination to the ability to throw in football in SSB Duri Galaxy U 17 players with a calculated r value = 0.508 and an r table value of 0.396 of 25.81% (3) There is a contribution of arm muscle power and eye and hand coordination to the ability to throw in football in SSB Duri Galaxy U 17 player with a calculated r value = 0.619 and an r table value of 0.396 of 38.32%.Key Words: Arm Muscle Power, Eye and Hand Coordination, Throw In Ability